EZCukai - Norizan, Saifulrizan; Abd Hamid, Nadiah; Ismail, Ida Suriya; Kassim, Zalilah @Azalilah; Abdillah, Azlin (2025)
An inventive digital learning tool called EZCukai was created to improve university students' taxation course learning experiences. Students find it difficult to understand complicated tax rules and processes since traditional tax education techniques are frequently too theoretical, out-of-date, and lack realworld applicability. In order to overcome these obstacles, EZCukai provides a user-friendly, interactive website with bilingual material (in both English and Bahasa Malaysia), real-time updates on Malaysian tax laws, and interactive learning resources including self-assessment tests and e-filing simulations. The app also incorporates engaging tutorials and flexible, self-paced learning modules that allow students to explore tax concepts in a more accessible and practical manner. By bridging the gap between theory and real-world application, EZCukai not only improves academic performance but also equips students with relevant skills for future professional roles in the field of taxation.